Applicaton of parameters of voice singal autoregressive models to solve speaker recognition problems - Novikov, Evgeny; Trubitsyn, Vladimir (Journal of Science and Technology on Information security, 2020)
<a title="" href="file:///C:/Users/Administrator.7WDDMINYQZ9PO37/Desktop/22019/3.%20Applicaton%20of%20parameters%20of%20voice%20singal%20autoregressive%20models%20to%20solve%20speaker%20recognition%20problems.docx#_ftn1"> Abstract— An approach to the formation of the voice signal (VS) informative features of the Vietnamese language on the basis of stationary autoregressive model coefficients is described. An original algorithm of VS segmentation based on interval estimation of speech sample numerical characteristics was developed to form local stationarity areas of the voice signal. The peculiarity is the use of high order autoregressive coefficients, the set of which is determined on the basis of discriminant analysis. Tóm tắt— Bài báo xem xét cách hình thành các đặc tính thông tin tín hiệu thoại của tiếng Việt trên cơ sở mô hình hệ số tự hồi quy cố định. Một thuật toán nguyên thủy cho việc phân chia tín hiệu thoại trên cơ sở ước lượng khoảng cách của các đặc điểm của số mẫu giọng nói đã được phát triển, để hình thành các vùng cố định cục bộ của tín hiệu thoại. Điểm đặc biệt trong cách tiếp cận là sử dụng các hệ số tự hồi quy bậc cao, mà tập của chúng được xác định trên một cơ sở của các phân tích phân biệt.